PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN BANTUAN TRAINER DAN KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XI TITL SMK N 1 DENPASAR - Sundari, Ni Komang Ayu; Agung, Anak Agung Gede; Widiana, I Wayan (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to determine the effect of the learning modelProblem Based Learning with the help of trainers and teacher pedagogic competencies on student learning outcomes in the subject of Class XI TITL Electrical Motor Installation at SMK Negeri 1 Denpasar. This type of research is included in the type of researchpre-experiment. The population in this study amounted to 44 people. The sample in this study were 40 people who were determined by techniquesimple random sampling. Data collection was carried out by distributing questionnaires and conductingpretest before experiment andposttest after carrying out the experiment. Data analysis was performed using a one-way covariance analysis technique. The results of the study show that: (1) there is a significant influence from the application of the learning modelProblem Based Learning at the price of Fcount= 280.382, p = 0.000. (2) After the pedagogic competence is controlled, there is a significant influence from the application of the learning modelProblem Based Learning with the help of a trainer indicated by price Fcount=294.285, p=0.000.